The Impact of Parity on Pariental Rupture Incidence Among Delivering Mothers at Clinic Alya Medica - Maulidianingtiyas, Maulidianingtiyas; Keswara, Nila Widya (CV. Publikasi Indonesia, 2026)
Childbirth is the process of expelling the products of conception through the birth canal or with medical assistance. Vaginal delivery may result in perineal rupture due to tearing of the birth canal tissues, which can contribute to maternal morbidity and increase the risk of maternal mortality. Several factors are associated with the occurrence of perineal rupture, including neonatal birth weight, maternal age, and parity. This study aimed to determine the relationship between parity and the incidence of perineal rupture. This study employed a quantitative approach with a correlational research design. The results showed that there was no significant relationship between parity and the incidence of perineal rupture. These findings indicate that parity alone may not be a determining factor in the occurrence of perineal rupture during vaginal delivery, and that other factors may play a more important role.